Considering Restorative Justice in Criminal Cases Involving Indonesian National Armed Forces Personnel - Goeniswara, Dinda; Yitawati, Krista; Chairani, Mierza Aulia (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
This study is motivated by the evolving paradigm in criminal justice, which is no longer solely oriented toward punishment but increasingly emphasizes the restoration of social relationships through a restorative justice approach, including within the military justice system. The research aims to analyze the implementation of restorative justice in military criminal cases adjudicated by the Madiun III-13 Military Court and to examine the legal considerations of the panel of judges in applying this approach in Decision Number 26-K/PM.III-13/AD/VII/2025 concerning fraud committed by a member of the Indonesian National Armed Forces (TNI). This study employs a normative legal research method using statutory and case-based approaches, supported by the analysis of judicial decisions and relevant empirical data related to military justice practices. The findings indicate that restorative justice was implemented through a mutual agreement between the perpetrator and the victim, accompanied by a mechanism for compensating the victim’s losses, while maintaining the principles of military discipline. Accordingly, restorative justice can be proportionally integrated into the military criminal justice system.